Aplicación del uso de la ceniza de la cascarilla de arroz para la elaboración de bloques de hormigón - Burgos García, Diego Efrén (2025)
This study investigates the potential use of rice husk ash (RHA) as a supplementary material in the production of concrete with a compressive strength of 210 kg/cm². This by product of the rice industry is a material that offers both environmental and structural benefits, as it reduces the use of cement and thus CO₂ emissions. The study examines the physical and chemical properties of the ash, emphasizing its pozzolanic activity, which enhances the compressive strength of concrete and improves its durability against corrosive agents. The research encompasses an assessment of the influence of varying ash concentrations in the concrete mixture on its mechanical attributes. Laboratory investigations have demonstrated that the incorporation of CCA can substitute for up to 10% of the cementitious material without impairing the quality of the concrete. Furthermore, a comparative analysis is conducted between the properties of traditional and ash-modified concrete, with the latter exhibiting favorable results in terms of strength and sustainability. Furthermore, the incorporation of CCA is consistent with the prevailing trends in sustainable construction, whereby industrial waste is repurposed and the environmental impact of building projects is minimized.